Integration of Decentralized Clinical Data in a Data Warehouse - Hanß, S.; Schaaf, T.; Wetzel, T.; Hahn, C.; Schrader, T.; Tolxdorff, T. (Methods of Information in Medicine, 2009)
Objectives: In this paper we present a general concept and describe the difficulties for the integration of data from various clinical partners in one data warehouse using the Open European Nephrology Science Center (OpEN.SC) as an example. This includes a requirements analysis of the data integration process and also the design according to these requirements.Methods: This conceptual approach based on the Rational Unified Process (RUP) and paradigm of Service-Oriented Architecture (SOA).Results: Because we have to enhance the confidence of our partners in the OpEN.SC system and with this the willingness of them to participate, important requirements are controllability, transparency and security for all partners. Reusable and fine-grained components were found to be necessary when working with diverse data sources. With SOA the requested reusability is implemented easily.Conclusions: A key step in the development of a data integration process within such a health information system like OpEN.SC is to analyze the requirements. And to show that this is not only a theoretical work, we present a design – developed with RUP and SOA – which fulfills these requirements.
Keywords: Data storage and retrieval; multicenter studies as topic; information management; software design